Extraordinary sensitivity in optical microfiber based refractive index sensors near the turning point of turning point of effective group index difference - Li, Kaiwei (2017)
We show that optical microfiber coupler sensors operating near the dispersion turning point can achieve ultrahigh refractive index (RI) sensitivity at RI around 1.33. It opens up new opportunities to ultra-sensitive biochemical sensing.